Pengaruh Penggunaan Software Keuangan (Accurate), dan Kemudahan Pengguna Terhadap Kualitas Laporan Keuangan Pada UMKM di Banjarmasin Timur - putri rahmayanti, nida; Anastasia, Maria; Yousida, Imawati; Istiazah (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The purpose of this study is to analyze the impact of the use of financial software (accuracy) and its usability on the quality of financial reporting. This study involved 87 people and used SPSS version 16 statistical tool. The results of the study showed that the use of financial software (accuracy) has a partial impact on the quality of financial reporting of SMEs in East Banjarmasin, and ease of use also partially affects the quality of financial reporting of SMEs in East Banjarmasin the region.